Penerapan Manajemen Pasien Safety Terhadap Keselamatan Pasien Post Operasi Fraktur Di Rsu Sundari Medan - Rizki, Lina; Sahfitri Siregar, Evi; Triana, Heni (JINTAN: Jurnal Ilmu Keperawatan, 2025)
One strategy to provide better patient service is patient safety. To detect and manage patient risks, report and analyze events, limit risks, and eliminate errors through action or inaction, patient safety assesses various types of risk assessments. A fracture is a break in bone continuity that occurs when a normal bone experiences great strain. This study aims to explain the relationship between patient safety after fracture surgery and Sundari RSU patient safety management procedures. The research design of this study is correlational analysis research.  RSU Sundari Medan was the location for this investigation. Forty-four respondents with post-operative fractures were the research sample with Cluster sampling. Bivariate analysis uses the product moment statistical test. Results and Analysis: Based on the results of bivariate analysis using the product moment test with a confidence level of 5% (α=0.05), the p value was 0.000, so the p value <0.05) which means that H0 was rejected, which means there is a relationship between the implementation of patient safety management and the safety of post-fracture surgery patients at Sundari General Hospital, Medan. The results of the study show a relationship between the implementation of patient safety management and the safety of post-fracture surgery patients at Sundari Hospital, Medan.